Interspecies interactions and biofilm development in a three-species biofilm model - Goh, Yu Fen (Nanyang Technological University, 2023)
Bacteria frequently live in multispecies biofilms where the organismal composition is largely influenced by the interspecies interactions. These interactions are genetically determined and the presence of co-occurring species is likely to result in specific changes in gene expression, thereby defining the spatial organisation of the community members, shaping biofilm biomass and directing overall biofilm functions. Communal level gene expression allows the mixed species biofilms to display enhanced tolerance to environmental stresses and increased virulence. Given the complexity of the interspecies interactions, the underlying mechanisms responsible for these interdependent relationships requires further examination. The objective of this study was to examine the development of a three species biofilm model composed of Pseudomonas aeruginosa PAO1, Klebsiella pneumoniae KP-1 and Pseduomonas protegens Pf-5. When the biofilm was exposed to predation by the protozoa Tetrahymena pyriformis, the grazing resistant P. aeruginosa protected the sensitive members, primarily through the secretion of rhamnolipids, a glycolipid, and an unknown secondary factor which are both toxic to the protozoa. Targeted gene deletion as well as generating a transposon library were used to identify genes of P. aeruginosa that were responsible for defending against protozoan predation. The Pseudomonas Quinolone Signal (PQS), a quorum sensing molecule, was shown to have toxicity against T. pyriformis. The exogeneous addition of PQS to the biofilm restored biofilm toxicity in the absence of rhamnolipids. The genes of P. protegens that mediate mixed species biofilm formation were further explored. For P. protegens, a total of eight genes, which were differentially expressed in the community, were compared for growth in a mixed community against monospecies biofilm. Among those highly induced genes, many belonged to the family of domain of unknown function (DUF) with no characterised function. The genes had no role on the utilisation of different substrates and planktonic metabolism of P. protegens. However, the species composition of the mixed community shifted when the mutants were grown in the community, either as planktonic cells or a biofilm. For example, confocal imaging showed that the deletion of the DUF genes changed the biovolume of the mixed species biofilm significantly. Thus, the data suggested that these uncharacterised genes are involved in shaping the mixed species biofilm development. To further explore P. protegens genes involved in community biofilm formation, a genome wide screen using TraDIS was undertaken. TraDIS analysis indicated that flagellar assembly, two component systems (TCS), chemotaxis were non-essential for both single and mixed species biofilm development. In contrast, oxidative phosphorylation was essential for mixed species biofilm development. Mutants in these candidate genes were generate and substituted for the parental strains in the community biofilms. Deletion of genes PFL_3355, pfeA and pstS, resulted in a change in species composition, but not total biofilm biovolume. Conversely. deletion of nuoA gene, involved in the first step of oxidative phosphorylation, resulted in a significant reduction of the biofilm biovolume for the community and composition change. In conclusion, this study provides further insights into the molecular mechanisms driving mixed species biofilm formation and the dynamics of community interactions.